2022
DOI: 10.1002/aelm.202101261
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Device Model for Organic Light‐Emitting Diodes Based on Thermally Activated Delayed Fluorescence

Abstract: have the drawback of using expensive, environmentally unfriendly heavy-metal complexes. In 2012, a new class of fully organic OLED materials emerged using thermally activated delayed fluorescence (TADF). [3,4] Here, the small singlet-triplet energy gap allows for efficient conversion from triplets to singlets on the same molecule, i.e., efficient reverse intersystem crossing (rISC) prompted by thermal energy. Therefore, while retaining the theoretically achievable 100% IQE, the necessity of an added toxic heav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…The EQE gradually increases to its maximum at a few hundreds of cd m −2 , then starts to roll off because of triplet–triplet annihilation. [ 32 ] The maximum EQE for the device with the first‐order cavity ( L = 85 nm) is ≈19%, while it is as high as 16–17% for devices with the second‐order cavity ( L = 300 nm). Thus, only a marginal EQE reduction is induced when extending the optical cavity, though the luminous efficacy has a larger decrease because of increased driving voltages, as shown in Figure S3 (Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…The EQE gradually increases to its maximum at a few hundreds of cd m −2 , then starts to roll off because of triplet–triplet annihilation. [ 32 ] The maximum EQE for the device with the first‐order cavity ( L = 85 nm) is ≈19%, while it is as high as 16–17% for devices with the second‐order cavity ( L = 300 nm). Thus, only a marginal EQE reduction is induced when extending the optical cavity, though the luminous efficacy has a larger decrease because of increased driving voltages, as shown in Figure S3 (Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…To analyze the EQE versus voltage characteristics in more detail, we have simulated the OLEDs with a recently developed drift‐diffusion model for TADF OLEDs. [ 41 ] First, the J – V characteristics are simulated based on the electron and hole mobility obtained from the charge‐transport measurements. The drift‐diffusion simulations then solve the recombination rate, and therefore exciton density, as a function of position in the device.…”
Section: Resultsmentioning
confidence: 99%
“…[78] Further characterization including quantum-chemical studies suggested that water-oxygen complexes cause electron trapping. [78][79][80][81] In its neutral state, this complex is only weakly bound. Charge detrapping effectively deactivates the trap.…”
Section: Trap-limited Charge Transport Studiesmentioning
confidence: 99%